Metabolic Profiling of Hoodia, Chamomile, Terminalia Species and Evaluation of Commercial Preparations Using Ultrahigh-Performance Liquid Chromatography Quadrupole-Time-of-Flight Mass Spectrometry - Avula, Bharathi; Wang, Yan-Hong; Isaac, Giorgis; Yuk, Jimmy; Wrona, Mark; Yu, Kate; Khan, Ikhlas A. (Planta Medica, 2017)
Ultrahigh-performance liquid chromatography quadrupole-time-of-flight mass spectrometry (UHPLC-QToF-MS) profiling was used for the identification of marker compounds and generation of metabolic patterns that could be interrogated using chemometric modeling software. UHPLC-QToF-MS was used to generate comprehensive fingerprints of three botanicals (Hoodia, Terminalia, and chamomile), each having different classes of compounds. Detection of a broad range of ions was carried out in full scan mode in both positive and negative modes over the range m/z 100–1700 using high-resolution mass spectrometry. Multivariate statistical analysis was used to extract relevant chemical information from the data to easily differentiate between Terminalia species, chamomile varieties, and quality control of Hoodia products. Using nontargeted analysis, identification of 37 compounds contributed to the differences between Terminalia species, 26 flavonoids were identified to show the differences between German and Roman chamomile, and 43 pregnane glycosides were identified from Hoodia gordonii samples. The UHPLC-QToF-MS-based chemical fingerprinting with principal component analysis was able to correctly distinguish botanicals and their commercial products. This work can be used as a basis to assure the quality of botanicals and commercial products.
Keywords: metabolomics; UHPLC-QToF-MS; Hoodia gordonii; Matricaria chamomilla; Anthemis nobilis; Terminalia chebula; Terminalia bellirica; Terminalia arjuna; principal component analysis